The lncRNA SLNCR1 Mediates Melanoma Invasion through a Conserved SRA1-like Region - Karyn Schmidt; Cailin E. Joyce; Frank Buquicchio; Adam Brown; Justin Ritz; Robert J. Distel; Charles H. Yoon; Carl D. Novina (Cell Reports, 2016)
Long non-coding RNAs (lncRNAs) have been implicated in numerous physiological processes and diseases, most notably cancers. However, little is known about the mechanism of many functional lncRNAs. We identified an abundantly expressed lncRNA associated with decreased melanoma patient survival. Increased expression of this lncRNA, SLNCR1, mediates melanoma invasion through a highly conserved sequence similar to that of the lncRNA SRA1. Using a sensitive technique we term RATA (RNA-associated transcription factor array), we show that the brain-specific homeobox protein 3a (Brn3a) and the androgen receptor (AR) bind within and adjacent to SLNCR1’s conserved region, respectively. SLNCR1, AR, and Brn3a are specifically required for transcriptional activation of matrix metalloproteinase 9 (MMP9) and increased melanoma invasion. Our observations directly link AR to melanoma invasion, possibly explaining why males experience more melanoma metastases and have an overall lower survival in comparison to females.